Tanggung Jawab Gereja Membangun Eco Tourism: Studi Kasus Sampuren Sikulikap, Desa Doulu Kabupaten Tanah Berastagi, Sumatera Utara - Lisda waty Harianja (Jurnal Pendidikan Agama dan Teologi, 2024)
The church is faced with an urgent responsibility to address the environmental crisis by building awareness of eco-tourism. By promoting eco-tourism as a tool to preserve nature and support sustainable development, the church not only provides theological understanding but also acts as a real agent of change in supporting environmental conservation efforts. A literature review of environmental ecology theory, eco-tourism theory, and Christian religious views provides a foundation for understanding human behavior towards nature. This research, using a descriptive qualitative method, combines literature analysis with the author's field experience to formulate a theoretical proposal. The church is considered to have a crucial responsibility in protecting the environment and building eco-tourism by supporting environmental programs, collaborating with NGOs, providing environmental education through worship, playing an active role in commemorating environmental days, and taking concrete steps in the development of sustainable eco-tourism. Conclusions highlight three concepts of the human view of the environment, with humans together with nature approaching the values of Christian eco-theology, while suggestions include church support on government environmental programs and close cooperation with NGOs to raise the environmental awareness of its members.